A new species of Peucedanum (Apiaceae) from Korea - Kim, Kyeonghee; Kim, Chan-Soo; Oh, Sang-Hun; Park, Chong-Wook (Phytotaxa, 2019)
A new species, Peucedanum chujaense K. Kim, S.-H. Oh, C.-S. Kim & C.-W. Park (Apiaceae), is described and illustrated. The new species distributed in the Chuja Islands off the north coast of Jeju Island in South Korea. It is morphologically similar to P. litorale, but is distinct from the latter in having 2-pinnate leaves (vs. 1-pinnate leaves), conspicuous calyx teeth 0.4–1 mm long (vs. minute calyx teeth 0.1–0.3 mm long), 20–24 (vs. 10–18) flowers per umbellet, seeds oblong (vs. semicircular) in cross section.